Pengembangan Ekosistem Kewirausahaan di Perguruan Tinggi melalui Inkubasi Bisnis Mahasiswa - Ibadurrahman, Ibadurrahman; Wahira, Wahira (Universitas Negeri Gorontalo, 2025)
This study is a literature review that examines various research findings related to the development of an entrepreneurial ecosystem in higher education through a student business incubation model. The analysis indicates that the entrepreneurial ecosystem on campus plays a role in fostering entrepreneurial intentions and competencies among students. Key influencing factors include access to funding, government policy support, entrepreneurship education and training, and the presence of active business incubators and networks with industry, emphasize that business incubators serve as a strategic tool for developing competent and adaptable young entrepreneurs to market challenges. Meanwhile, other studies highlight the importance of collaboration between universities, industry, and government agencies in strengthening the pillars of the entrepreneurial ecosystem. The methodological approaches used in these studies, including quantitative, qualitative, and mixed methods, generally yield consistent findings regarding the significant contribution of the campus environment in shaping students' entrepreneurial intentions. This synthesis suggests that the success of the entrepreneurial ecosystem in higher education is determined by the integration of institutional policies, the implementation of incubation programs, and human resource support oriented toward sustainable entrepreneurial practices.